2022
DOI: 10.3389/fonc.2022.919278
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Clonal Evolution on Progression, Blood Parameters, and Response to Therapy in Multiple Myeloma

Abstract: IntroductionA variety of biomarkers are considered for diagnosis (e.g., β2-microgobulin, albumin, or LDH) and prognosis [e.g., cytogenetic aberrations detected by fluorescence in situ hybridization (FISH)] of multiple myeloma (MM). More recently, clonal evolution has been established as key. Little is known on the clinical implications of clonal evolution.MethodsWe performed in-depth analyses of 25 patients with newly diagnosed MM with respect to detailed clinical information analyzing blood samples collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Studying clonal evolution in more detail, a diverse set of analyses can be performed: the model of clonal evolution (linear vs. branched dependent vs. branched independent; of note, neutral and punctuated evolution will be considered special cases of branched and linear evolution) [ 8 , 9 ] can be determined; correlation to blood parameters, therapy resistance, and disease progression investigated [ 10 ]; and patterns characterizing subgroups of patients explored. For example, by detailed analysis of clonal evolution, evidence was found that relapsing BL is associated with the presence of clones, featuring double-hit events in TP53 [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studying clonal evolution in more detail, a diverse set of analyses can be performed: the model of clonal evolution (linear vs. branched dependent vs. branched independent; of note, neutral and punctuated evolution will be considered special cases of branched and linear evolution) [ 8 , 9 ] can be determined; correlation to blood parameters, therapy resistance, and disease progression investigated [ 10 ]; and patterns characterizing subgroups of patients explored. For example, by detailed analysis of clonal evolution, evidence was found that relapsing BL is associated with the presence of clones, featuring double-hit events in TP53 [ 8 ].…”
Section: Introductionmentioning
confidence: 99%